Tunnel Behaviour Caused by Basement Excavation in Clay. (30th March 2021) - Sun, Huasheng; Zhang, Jihua; Zhao, Guodong; Wang, Hao
Abstract : Many researchers have investigated the effect of basement excavation on tunnel deformation. However, the influence of consolidation on the interaction of basement-tunnel-soil is rarely considered or systematically studied in clay. In this study, three-dimensional coupled-consolidation finite element analyses were conducted to investigate the effect of consolidation on the tunnel response to excavation. An advanced nonlinear constitutive model was adopted, and numerical parametric investigations were conducted to study the effect of the excavation depth, tunnel stiffness, soil permeability coefficient, and consolidation time on the tunnel response. The results revealed that the basement excavation led to stress release, which caused tunnel heave. Owing to the dissipation of excess negative pore water pressure, the tunnel heave further increased to become approximately twice as large compared with that observed when the foundation pit excavation had just been completed. As the consolidation time increased, the longitudinal tunnel heave and tunnel diameter change caused by the foundation pit excavation gradually increased, but the growth rate was slower down. When the consolidation time changed from 50 days to 150 days, the maximum tunnel heave at the crown and the maximum tunnel diameter change increased by 1.18 and 1.48 times, respectively. The soil's permeability coefficient did not have a significant effect on the tunnel heave at the crown nor on the tunnel diameter change. The results obtained by this study are expected to be useful as an engineering reference for the analysis of soil structure problems in clay.